Will Barnet - Barnet, Ona; Stavitsky, Gail 1954-; Green, Christopher T. 1990-; Nicoll, Jessica F. (The Artist Book Foundation, 2024)
"Will Barnet's artistic career as a painter and printmaker spanned nearly eight decades of continuous creativity. Few artists, other than perhaps Picasso or Monet, can claim such an extended period of uninterrupted and innovative art making. From the darkness of the Great Depression to the opening decade of the twenty-first century, his oeuvre reflects his unique interpretation of the art world's evolving genres: Social Realism, Modernism, Abstract Expressionism, and ultimately representational Minimalism with the human figure as his primary subject. Barnet was devoted to making art every day and worked diligently even at the very end of his life. "The Old Masters are still alive after 400 years, and that's what I want to be," he once said."
Keywords: Barnet, Will -- 1911-2012; Barnet, Will / 1911-2012 / Criticism and interpretation; ART / American / General; ART / Individual Artists / Monographs; Barnet, Will / 1911-2012 / https://id.oclc.org/worldcat/entity/E39PBJjxxFRC8x9RX8QxkBHt8C; Criticism, interpretation, etc; Bildband; Biografie